2002
DOI: 10.1161/01.hyp.0000022805.11288.7f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pravastatin on Proteinuria in Patients With Well-Controlled Hypertension

Abstract: Abstract-Proteinuria is an important risk factor for cardiovascular and renal morbidity and mortality. The effects of 3-hydroxy-3-methyglutaryl coenzyme A reductase inhibitor (statin) therapy on proteinuria in normolipidemic patients with well-controlled hypertension have not been studied. A total of 63 normolipidemic (total cholesterol Ͻ240 mg/dL) and proteinuric (300 to 3000 mg/d) patients with well-controlled blood pressure (Ͻ140/90 mm Hg) were randomized to receive either placebo (nϭ32) or pravastatin (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 41 publications
8
52
1
Order By: Relevance
“…[23][24][25] In contrast, studies including normotensive individuals or well-controlled hypertensive patients were unable to demonstrate a statin-induced blood pressure-lowering effect. 26,27 In agreement with these latter studies, no blood pressure-lowering effect of fluvastatin was observed in our normotensive FH subjects. The reason for the absence of a blood pressure-lowering effect despite the decrease in Ang II sensitivity is unknown.…”
Section: Van Der Linde Et Al Ldl Cholesterol and Ang II Sensitivitysupporting
confidence: 92%
“…[23][24][25] In contrast, studies including normotensive individuals or well-controlled hypertensive patients were unable to demonstrate a statin-induced blood pressure-lowering effect. 26,27 In agreement with these latter studies, no blood pressure-lowering effect of fluvastatin was observed in our normotensive FH subjects. The reason for the absence of a blood pressure-lowering effect despite the decrease in Ang II sensitivity is unknown.…”
Section: Van Der Linde Et Al Ldl Cholesterol and Ang II Sensitivitysupporting
confidence: 92%
“…Immunoglobulins have been found in the urine of human patients with glomerular disease in a variety of disorders (4,3,25,29). Moreover, several infectious diseases are diagnosed by the finding of specific antibodies in urine, such as Helicobacter pylori infection (18), filariasis (17), or schistosomiasis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-and interassay coefficients of variation were 4.5% and 6.6%, respectively. Total serum cholesterol and triglyceride levels were measured by standard enzymatic techniques (18).…”
Section: Methodsmentioning
confidence: 99%
“…Statin therapy has many effects independent of changes in plasma cholesterol concentrations (18). Lipophilic statins have been shown to attenuate in vitro cellular hypertrophy (21,27).…”
mentioning
confidence: 99%